Dense films formed during Ti anodization in NH4F electrolyte: Evidence against the field-assisted dissolution reactions of fluoride ions - Qinyi Zhou; Mengmeng Tian; Zongrong Ying; Yuxin Dan; Fengrui Tang; Jianpeng Zhang; Junwu Zhu; Xufei Zhu (Electrochemistry Communications, 2020)
Nowadays, the formation mechanism of anodic titanium dioxide nanotubes (ATDNs) is still controversial. Although the field-assisted dissolution reactions are widely cited, more and more experimental facts cannot be explained. In this work, the anodizing processes of Ti in three different electrolytes containing 0.7 wt% NH4F and 1.8 vol% H2O are carefully compared. Although the anodizing current–time curves obtained in ethanol electrolyte are similar to those of ethylene glycol, ATDNs are obtained in ethylene glycol but dense TiO2 films are obtained in ethanol. This interesting result contradicts the field-assisted dissolution reactions of fluoride ions. Based on the oxygen bubble mould and the ionic current and electronic current model, a reasonable interpretation for this result is presented. The low conductivity of the ethanol electrolyte results in small ionic current, which leads to slow growth of the oxide, so the embryos of nanotubes cannot be formed around the oxygen bubbles. In addition, the rises in the current–time curves of ethanol electrolyte are due to the generation of electronic current which leads oxygen bubbles to release from the surface of anodic films directly. This important conclusion is confirmed by ATDNs obtained in the mixture of ethanol and ethylene glycol electrolyte containing the same concentration of fluoride ions. Keywords: Dense films, Anodization, Electronic current, Ionic current, Formation mechanism